Head Circumference Growth Is Enhanced by SMOFlipid in Preterm Neonates - Bin-Nun, Alona; Kassirer, Yair; Mimouni, Francis B.; Shchors, Irina; Hammerman, Cathy (American Journal of Perinatology, 2019)
Background Suboptimal fat intake during the early postnatal weeks significantly affects brain growth and maturation. Studies to date have focused on the quantity rather than the quality of fat intake.Objective We hypothesized that early nutrition of premature neonates should also include optimization of the type of fat intake, and thus those receiving SMOFlipid, a balanced multicomponent lipid emulsion, would have improved head growth as measured by head circumference (HC) at discharge.Study Design We retrospectively reviewed HC in infants weighing <1,500 g who were hospitalized for two or more weeks during a 20-month period, in which all preterm infants received fat as Lipofundin, and the following 20-month period, in which all such infants received SMOFlipid.Lipids were dosed up to 3 g/kg/day and reduced as enteral nutrition progressed. Parenteral fish oil (Omegaven) was permitted as rescue therapy during both periods.Results Period 2 infants had better head growth (0.79 [0.69,0.90] vs. 0.75 [0.64,0.86] cm/week; p = 0.0158). More infants reached discharge with an HC of ≥50 percentile (51 vs. 31%; p = 0.0007), and fewer infants had an HC of ≤3 percentile (11 vs. 14%; p = 0.023). Median length of stay was reduced by more than 1 week.A multivariable regression was performed using the weekly increase in HC as the dependent variable, and the time epoch, birth weight, gestational age, hospitalization days, and gender as independent variables. Only the time epoch and days of hospitalization were significant (both p < 0.0001).Conclusion Our data offer preliminary evidence of improved brain growth in those receiving a balanced lipid emulsion as compared with a soybean oil emulsion.
Keywords: perinatal nutrition; total parenteral nutrition; long-chain polyunsaturated fatty acids; head circumference; SMOFlipid